COSTLY-DEFENSE SYSTEMS VERSUS PRODUCTIVE INVESTMENTS: THE CASE OF SINGAPORE’S 1st GENERATION MILITARY BUILD-UP (THE 1960s-1980s) - Wirawan Hanindito Wicaksono; Ruslan Arief (Jurnal Pertahanan: Media Informasi ttg Kajian & Strategi Pertahanan yang Mengedepankan Identity, Nasionalism & Integrity, 2022)
Choosing a costly defense over an economically productive investment is always a nightmare for national policymakers. Despite the dilemma, Singapore came up as an anomaly with its decision in investing a remarkable amount of defense budget, reaching 4.5% of its GDP (Gross Domestic Product) and ranging around 15-30% of its annual government spending and still succeeding in developing its economy, while some do not. Therefore, drawing from what happened in the early period of Singaporeâ€™s independence, this study aims to figure out how the country justified its decision to choose a costly defense investment over a productive investment during this period and how the Singapore government decided to spend almost 40% of its annual budget on defense. Through historical analysis and literature studies, this study finds that the decision to choose a costly defense investment over an economically productive investment is justifiable under specific circumstances: first, when a nation deals with threats that would cost the nation future and survivability; second, the ability to implement the policy effectively and efficiently; third, is the ability to set how much is enough, the top limit of defense investment; and fourth, the existence of potential economic benefits.Â